Inflammatory myofibroblastic tumour of the mandible – A case report (Update Dental College Journal, 2020)
Inflammatory myofibroblastic tumour (IMT) is an extremely rare, benign softtissue lesion of unknown aetiology and pathogenesis that mimics malignant lesions clinically and radiologically found in the maxillofacial region. It occurs primarily in the lungs but occurred in other extra-pulmonary sites. Histologically these lesions appear as an inflammatory infiltrate within a variable of myofibrotic background. The current mode of treatment for inflammatory myofibroblastic tumour (IMT) is surgical excision with regular follow up. In this case report a 40 years old female presented with an intraosseous inflammatory myofibroblastic tumour (IMT) in the left side of mandible which was treated by surgical excision of the lesion. This article also describes the clinicopathological features and treatment of a case of inflammatory myofibroblastic tumour (IMT) of the mandible.Update Dent. Coll. j: 2020; 10 (1): 21-24